The Effect of Educational Videos on Knowledge and Attitudes of Healthy Eating Patterns to Prevent Anemia in Adolescent Females - Halimah Muhtar; Sheena Ramadhia Asmara Dhani (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anemia is a common health problem among adolescent girls and has a significant impact on learning concentration and productivity. One of the main contributing factors is an unhealthy dietary pattern. Educational videos are considered an effective medium to improve adolescents’ knowledge and attitudes regarding anemia prevention. To determine the effect of educational videos on knowledge and attitudes related to healthy eating patterns for anemia prevention among adolescent girls at SMP N 1 Cepogo. This study employed a quasi-experimental design with a pretest–posttest control group. A total of 100 female students were selected using proportionate stratified random sampling and divided into intervention and control groups. Data were collected using structured knowledge and attitude questionnaires. Instrument validity was tested using Pearson correlation, showing all items had correlation coefficients greater than the r-table value (r > 0.209; p < 0.05). Reliability testing demonstrated excellent internal consistency, with Cronbach’s alpha values of 0.961 for the knowledge questionnaire and 0.945 for the attitude questionnaire. Data analysis was conducted using the Wilcoxon Signed-Rank test. The control group showed no significant changes in knowledge (p = 0.472) or attitude (p = 0.239). In contrast, the intervention group showed significant improvements in both knowledge (p = 0.05) and attitude (p = 0.00). The mean knowledge score increased from 5.33 to 10.44, while the mean attitude score increased from 35.56 to 50.93. Educational videos are effective in significantly improving knowledge and attitudes toward healthy dietary patterns for anemia prevention among adolescent girls.